Fe76-xCoxSi2B21Cu biphase nanocrystalline powder with excellent electromagnetic absorption performance
By preparing Fe76-xCoxSi2B21Cu biphasic nanocrystal powder, the ball milling and annealing process are used to solve the problems of insufficient absorption performance and easy corrosion of traditional magnetic metal powders, and excellent electromagnetic absorption performance and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202510086823.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing magnetic metal micropowders have problems such as short effective absorption bandwidth, low reflection loss and easy corrosion, which limits their widespread use in various fields.
A biphasic nanocrystal powder of Fe76-xCoxSi2B21Cu was used to melt the alloy under the protection of an inert atmosphere, and amorphous strips were prepared, followed by ball milling and annealing to obtain biphasic nanocrystal powder.
The electromagnetic absorption performance with the strongest reflection loss (RL) value up to -59.51dB and the optimal effective bandwidth up to 7.68GHz is achieved, covering the X and Ku bands, and improving the corrosion resistance of the material.
Smart Images

Figure CN119897458A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electromagnetic absorption materials, and particularly relates to a Fe 76- x Co x Si 2 B 21 Cu dual phase nanocrystalline powder. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Electromagnetic absorption materials can absorb the energy of electromagnetic waves projected onto their surfaces, and convert the electromagnetic wave energy into heat or other forms of energy through various losses of the materials. Ideal electromagnetic absorption materials should have the characteristics of thin materials, light weight, wide frequency band, and strong strength. In the past few decades, researchers have explored a variety of electromagnetic absorption materials, among which magnetic metal powder is a very important type of electromagnetic absorption material. Magnetic metal powder has good soft magnetic properties and large magnetic permeability, and mainly loses electromagnetic waves through mechanisms such as eddy current loss and natural resonance loss. However, traditional magnetic metal powder has high conductivity and a strong skin effect. The incident electromagnetic wave can only exist on the surface of the electromagnetic absorption material and cannot effectively enter the interior of the material, resulting in a short effective absorption bandwidth and low strongest reflection loss. At the same time, the problems of easy corrosion and poor environmental adaptability of traditional magnetic metal powder limit its wide use in various fields.
[0004] Compared with traditional magnetic metal powders, dual-phase nanocrystalline alloy powders have the special structure of nanocrystalline phase and amorphous matrix. The atoms in the amorphous phase do not have long-range order and periodic regular arrangement in three-dimensional space, but are in a state of short-range order and long-range disorder, and there are no crystal defects such as dislocations and grain boundaries. It has excellent wear resistance and corrosion resistance and can adapt to complex and changeable external environments such as seawater. The soft magnetic nanocrystalline phase has high saturation magnetization and low coercive force, which improves the initial magnetic permeability and has strong magnetic loss capacity. At the same time, the non-metallic elements and amorphous phase contained in the dual-phase nanocrystalline alloy powder make its resistivity higher, inhibit eddy current loss, low dielectric constant, and optimize impedance matching ability. Therefore, dual-phase nanocrystalline alloy powder materials are promising candidate materials that have received more and more attention in the field of electromagnetic absorption. Zhang et al. prepared Fe by mechanical ball milling. 80.7 Si 4 B 13 Cu 2.3Nanocrystalline soft magnetic alloy powder was prepared and its electromagnetic wave absorption performance was studied. The results showed that the powder had excellent electromagnetic wave absorption performance in the x-band (8-12GHz), with the best reflection loss of -50.5dB and the best effective absorption bandwidth of 5.0GHz. Chen et al. prepared FeCrMoNiPBCSi amorphous powder by gas atomization and combined it with organic silicon to achieve good impedance matching and strong electromagnetic wave attenuation. The best reflection loss reached -60.3dB at 7.08GHz, but the best effective absorption bandwidth was only 2.30GHz, which could not meet the requirements of the new generation of electromagnetic absorption materials, and the composition of the dual-phase nanocrystalline alloy powder suitable for electromagnetic absorption was still unclear.
[0005] Patent CN110993239A discloses a method for preparing an iron-cobalt-based amorphous soft magnetic alloy, in which amorphous strips are prepared by a strip-spinning method, and then annealed to obtain strip-shaped samples, but the microwave absorption performance thereof still needs to be improved.
[0006] Patent CN109554635A discloses a method for preparing a porous amorphous soft magnetic composite material with strong microwave absorption performance. The amorphous strip is first placed in a ball mill for ball milling, and then etched to obtain porous amorphous powder, but its microwave absorption strength still needs to be improved.
[0007] In summary, the preparation of "thin", "light", "wide" and "strong" electromagnetic absorption materials often requires the coordination of alloy composition and preparation process to control the dual-phase nanocrystalline structure. However, the industry has not yet prepared an alloy material with both excellent broadband and super strong absorption performance. Summary of the invention
[0008] In order to solve the above problems, the present invention provides a Fe 76-x Co x Si 2 B 21 Cu two-phase nanocrystalline powder. The present invention successfully prepared a new type of two-phase nanocrystalline alloy powder electromagnetic absorption material with the strongest reflection loss (RL) value of up to -59.51dB and the best effective bandwidth of up to 7.68GHz (10.08-17.76GHz). Its special two-phase nanocrystalline structure achieves excellent impedance matching and electromagnetic attenuation, and also provides guidance for the research and development of electromagnetic absorption materials with better performance.
[0009] In order to achieve the above object, the present invention adopts the following technical solution:
[0010] The first aspect of the present invention provides a Fe 76-x Co x Si 2 B 21Cu dual-phase nanocrystalline powder, the chemical formula of the dual-phase nanocrystalline powder is Fe 76-x Co x Si 2 B 21 Cu, wherein x=0-10.
[0011] In some embodiments, x=0, 2, 4, 6, 8 or 10.
[0012] The second aspect of the present invention provides a Fe 76-x Co x Si 2 B 21 The preparation method of Cu dual-phase nanocrystalline powder comprises:
[0013] Under the protection of inert atmosphere, Fe, Co, Si, Cu and FeB are mixed and smelted to obtain Fe 76-x Co x Si 2 B 21 Cu alloy ingot;
[0014] Fe was prepared by single copper roller melt spinning process. 76-x Co x Si 2 B 21 Cu amorphous strip;
[0015] The Fe 76-x Co x Si 2 B 21 Cu amorphous strips were cut to less than 1 mm, ball-milled, and annealed to obtain Fe 76-x Co x Si 2 B 21 Cu dual-phase nanocrystalline powder;
[0016] Wherein, x=0-10.
[0017] In some embodiments, the mass fraction of Fe is 99.99% or more;
[0018] In some embodiments, the mass fraction of Co is 99.98% or more;
[0019] In some embodiments, the mass fraction of Si is 99.9999% or more;
[0020] In some embodiments, the mass fraction of Cu is 99.99% or more;
[0021] In some embodiments, in the FeB, the mass ratio of Fe to B is 5:1.
[0022] In some embodiments, the Fe 76-x Co x Si 2 B 21 The Cu amorphous strip has a thickness of 20-25 μm and a width of 1.5-2 mm.
[0023] In some embodiments, the ball milling is performed by vacuum ball milling.
[0024] In some embodiments, the vacuum ball milling conditions are: ball-to-material weight ratio of 30-32:1, rotation speed of 500-600 rpm, each rotation of 0.5-0.6h during the ball milling process, paused for 5-8min, and forward and reverse rotations were performed alternately.
[0025] In some embodiments, the annealing treatment is performed in an inert atmosphere, the annealing temperature is 673-678 K, and the annealing time is 1-1.5 h.
[0026] The second aspect of the present invention provides annealing and Co content in regulating Fe 76-x Co x Si 2 B 21 Application of Cu dual-phase nanocrystalline powder in microwave absorption properties.
[0027] The third aspect of the present invention provides the above-mentioned Fe 76-x Co x Si 2 B 21 Application of Cu dual-phase nanocrystalline powder in the preparation of electromagnetic absorption materials.
[0028] Beneficial effects of the present invention
[0029] (1) The present invention prepares a "thin", "light", "wide" and "strong" electromagnetic absorption material, and its special dual-phase nanocrystalline structure achieves excellent impedance matching and electromagnetic attenuation. The dual-phase nanocrystalline powder of the present invention has a maximum reflection loss (RL) value of -59.51dB at 12.32GHz, and an effective bandwidth of 7.68GHz (10.08-17.76GHz) at a thickness of 1.69mm, achieving absorption of half of the X-band and the entire Ku-band. The effective bandwidth at a thickness of 2.09mm is 5.12GHz (8.00-13.12GHz), covering the entire X-band. Excellent broadband and super-strong wave absorption performance is demonstrated at a thin thickness.
[0030] (2) Compared with the unannealed nanocrystalline powder, the annealed nanocrystalline powder in the present invention continues to maintain excellent wave absorbing performance, and the strongest reflection loss (RL) moves to the low frequency region.
[0031] (3) The preparation method of the present invention is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention, and do not constitute improper limitations on the present invention.
[0033] Figure 1 .Fe 76-x Co x Si 2 B 21 XRD spectra of Cu (x=0, 2, 4, 6, 8, 10): (a) alloy strip. (b) powder after ball milling for 90h. (c) powder annealed at 673K.
[0034] Figure 2 .Fe after ball milling and annealing 76-x Co x Si 2 B 21 The grain size of Cu (x=0,2,4,6,8,10);
[0035] Figure 3 .Fe 76-x Co x Si 2 B 21 DSC spectra of Cu (x = 0, 2, 4, 6, 8, 10): (a) alloy strip, (b) powder ball-milled for 90 h, (c) powder annealed at 673 K;
[0036] Figure 4 .Different states of Fe 76-x Co x Si 2 B 21 Crystallization enthalpy curves of Cu (x=0,2,4,6,8,10);
[0037] Figure 5 .SEM and EDS images of M6;
[0038] Figure 6 (a) and (b) are Fe before and after annealing. 76-x Co x Si 2 B 21 Particle size distribution of Cu (x = 0, 2, 4, 6, 8, 10) powder. (c) Fe 76-x Co x Si 2 B 21 Average particle size diagram of Cu (x=0,2,4,6,8,10) powder;
[0039] Figure 7 (a) M-Fe 76-x Co x Si 2 B 21 Cu and (b) A-Fe 76-x Co x Si 2 B 21 Magnetic hysteresis loops of two Cu powders;
[0040] Figure 8 .M-Fe 76-x Co x Si 2 B 21 Cu and A-Fe 76-x Co x Si 2 B 21 Electromagnetic parameters of two Cu powders;
[0041] Fig. 9 .M-Fe 76-x Co x Si 2 B 21 Cu and A-Fe 76-x Co x Si 2 B 21 Dielectric loss tangent tanδ of two Cu powders in the frequency range of 2-18 GHz ε and the magnetic loss tangent tanδ μ ;
[0042] Fig.10 .M-Fe 76-x Co x Si 2 B 21 Cu and A-Fe 76-x Co x Si 2 B 21 Cu powders in the frequency range of 2-18 GHz 0 curve;
[0043] Fig.11 .M-Fe 76-x Co x Si 2 B 21 Cu and A-Fe 76-x Co x Si 2 B 21 Contour plots of reflection loss of two Cu powders as a function of thickness and frequency;
[0044] Fig.12 .Specific RL of each powder min 、f m , Δf RL<-10 and d m value.
[0045] Fig.13 .Reflection loss corresponding to different thicknesses of M6 powder, change of impedance matching with frequency at different thicknesses, and attenuation coefficient α of M6 powder. DETAILED DESCRIPTION
[0046] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0047] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0048] Example 1
[0049] In an arc melting furnace with argon as the protective atmosphere, Fe (mass fraction 99.99%), Co (99.98%), Si (99.9999%), Cu (99.99%), and FeB (mass ratio 5:1) were fully melted to prepare a uniformly mixed Fe 76-x Co x Si 2 B 21 Cu (x = 0, 2, 4, 6, 8, 10) alloy ingots with a mass loss of less than 0.5%. Amorphous strips with a thickness of about 25 μm and a width of about 2 mm were prepared using a single copper roller melt spinning technique. The amorphous strips were cut to less than 1 mm using ceramic scissors, and the sheared Fe of different components was pulverized using a planetary ball mill. 76-x Co x Si 2 B 21 The Cu (x = 0, 2, 4, 6, 8, 10) strips were vacuum milled to obtain dual-phase nanocrystalline alloy powders M-Fe 76-x Co x Si 2 B 21 Cu, respectively (M0, M2, M4, M6, M8, M10), ball-to-material weight ratio 30:1, rotation speed 500rpm, in order to prevent the ball mill from overheating, every half hour of rotation during the ball milling process, pause for 5min, and alternate forward and reverse rotation. 76-x Co x Si2 B 21 A-Fe Cu(x=0,2,4,6,8,10) ball-milled powder was annealed at 673K in argon atmosphere for 1h to obtain 76-x Co x Si 2 B 21 Cu (x = 0, 2, 4, 6, 8, 10) powder, denoted as (A0, A2, A4, A6, A8, A10).
[0050] Example 2
[0051] The strips and powders prepared in Example 1 were tested, including:
[0052] The phase composition and microstructure of the ribbons and powders were characterized by X-ray diffraction (DMAX-2500PC) and transmission electron microscopy (JEOL JEM F200) with Cu-Ka radiation. The thermal properties of the alloys were studied by differential scanning calorimetry (DSC) at a heating rate of 20 k / min. The morphology of the powders was characterized by scanning electron microscopy (SEM) (G500). The particle size of the powders was then measured by a laser particle size distribution analyzer (Mastersizer 2000). The saturation magnetization (Ms) and coercive force (Hc) of the materials at a maximum applied magnetic field of 1.5 T at room temperature were studied by a vibrating sample magnetometer (Lakeshore-7404). The ground and annealed powders were mixed with paraffin in a weight ratio of 7:3 and pressed under a hydraulic press with a pressure of 1000 Pa for 5 s. Coaxial rings with an inner diameter of 3.04 mm and an outer diameter of 7.00 mm were prepared using the mold. The composite dielectric constant and permeability were measured using a vector network analyzer (E5071C) with the coaxial transmission method in the frequency range of 2-18 GHz.
[0053] Example 3
[0054] The X-ray diffractometer was used to analyze the different states of Fe 76-x Co x Si 2 B 21 The structural analysis of Cu(x=0,2,4,6,8,10) materials was carried out. Figure 1 (a) shows Fe 76-x Co x Si 2 B 21 The XRD patterns of Cu (x = 0, 2, 4, 6, 8, 10) alloy strips show the relationship between the microstructure evolution of the alloy and the Co composition. For alloy strips with different Co contents, they all show typical broad diffraction peak characteristics, forming an amorphous structure. However, the strips with lower Co content precipitate weak crystal peaks at the broad diffraction peaks. The results show that appropriate Co addition is beneficial to improve Fe76-x Co x Si 2 B 21 After 90h of mechanical ball milling, all powders precipitated α-FeCo phase and Fe 2 Phase B, such as Figure 1 As shown in (b), the main diffraction peak is relatively broad, and the ball-milled powder is partially crystallized. After annealing, the diffraction peak intensity increases, as shown in Figure 1 As shown in (c), this is due to the significant increase in the average grain size of the alloy powder and the increase in crystallinity. It is worth noting that the FCC phase precipitates after annealing. The average grain size of a-FeCo precipitates with different Co contents before and after annealing is estimated by the Scherrer equation (1) based on the half-peak width at the diffraction peak (110) in the X-ray diffraction pattern. Figure 2 As shown, the average grain size before annealing varies slightly with the Co content. After annealing, the average grain size increases significantly, but they are all nanoscale powders, indicating that the material can be regulated to precipitate nanocrystalline phases of different sizes by ball milling amorphous strips and annealing treatment.
[0055]
[0056] K is the Scherrer constant, D is the average thickness of the grain perpendicular to the crystal plane, B is the half-height width of the diffraction peak of the measured sample, θ is the diffraction angle, and γ is the X-ray wavelength, which is 0.154056 nm.
[0057] The Fe in different states was investigated by DSC. 76-x Co x Si 2 B 21 The thermal properties of Cu(x=0,2,4,6,8,10) materials were studied. Figure 3 (a) is a strip DSC curve. The results show that as the Co content increases, the crystallization process of the alloy changes from one peak to two peaks, where the first and second crystallization temperatures T x1 and T x2 They represent the precipitation of a-Fe(Co,Si) and Fe(Co) boride phases from the amorphous matrix. When the Co content is low, T x1 The disappearance of indicates the precipitation of a-Fe(Co,Si), which is consistent with the appearance of XRD diffraction peaks. As the Co content increases from x = 0 to x = 8, T x1 First decrease and then keep relatively stable, T x2 From 773K to 797K, △T(T x1 -T x2 ) means that the increase of Co content improves the thermodynamic stability of the amorphous component. Figure 4 Fe in different states76-x Co x Si 2 B 21 The exothermic enthalpy curves of Cu (x = 0, 2, 4, 6, 8, 10) materials show that as the Co content increases, the crystallization enthalpy area of the ribbon material increases first and then decreases, corresponding to the amorphous ratio first increasing and then decreasing, which also shows that the appropriate Co content is conducive to the formation of the amorphous phase. Compared with the ribbon, after 90h of mechanical ball milling, the exothermic enthalpy area on the DSC curve of each component has a significant decrease, such as Figure 3 (a), (b) and Figure 4 As shown, it shows that the crystallization degree of the alloy powder is higher after ball milling, and the alloy powder M-Fe 76-x Co x Si 2 B 21 The exothermic enthalpy area of Cu (x = 0, 2, 4, 6, 8, 10) increases with the Co content, and the exothermic enthalpy area is consistent with the change trend of the strip material, indicating that the strip containing more nanocrystalline phases still has more nanocrystalline phases after ball milling. 76-x Co x Si 2 B 21 Cu (x = 0, 2, 4, 6, 8, 10) powders further crystallize, and the crystallization exothermic peak is basically not observed on the DSC curve, such as Figure 3 As shown in (c), the present invention observes its microstructure through high-resolution TEM, and it can be found that the powder is still composed of amorphous and nanocrystalline dual phases.
[0058] Figure 5 The SEM and EDS images of M6 powder are shown in Figure 2. Figure 5 It can be seen that the powder particles mainly present two forms, flat flake form and uneven cluster form. The powder particle size is all below 100 microns, and the element distribution has good uniformity. The flat flake form of the mechanically ball-milled two-phase nanocrystalline powder has a large aspect ratio, which is beneficial to improve the surface dipole polarization and reduce eddy current loss, reduce the reflection of electromagnetic waves on the surface of the material, and thus improve the electromagnetic wave absorption performance of the material. This is caused by the crushing and cold welding effects during the ball milling process. The crushing action during the ball milling process causes the brittle crystallized particles to break into small particles. The small particles easily aggregate and adhere to larger particles, resulting in many uneven cluster-like particles. The special surface structure causes multiple reflections and scattering of the incident electromagnetic waves, which enhances the material's ability to resist electromagnetic wave losses. The particle size and average size distribution of the specific alloy powder before and after annealing are shown in the figure. Figure 6 As shown, the particle size curve is normally distributed. By contrast, it is found that the random aggregation of powder particles after annealing leads to a significant increase in size.
[0059] M-Fe76-x Co x Si 2 B 21 Cu and A-Fe 76-x Co x Si 2 B 21 The hysteresis loop of Cu two-phase nanocrystalline powder is shown in Figure 7 As shown. Figure 7 It can be seen that both powders exhibit excellent soft magnetic properties. The inset is a graph showing the variation of Ms and Hc with Co content. Figure 7 In (a), Ms increases slightly with the increase of Co content, then decreases and then increases, and the M4 powder reaches a maximum value of 175.14emu / g. Since the Ms of the alloy is mainly determined by its composition and microstructure, while Hc is affected by the grain size, defect concentration, preparation and heat treatment process. For nanocrystalline alloys, the Ms of the soft magnetic nanocrystalline phase is greater than the Ms of the amorphous phase. Therefore, the increase in α-FeCo nanocrystals with the increase of Co content promotes the exchange coupling between grains, resulting in a rapid increase in Ms. The decrease in Ms at M4 and M6 is due to the increase in amorphous phase. When the Co content is high, the coercivity will increase due to the corresponding increase in magnetostriction during crystallization. At the same time, according to the random anisotropy model, the change law of coercivity with grain size is roughly: Hc∝D 6 The combined effect of the two causes Hc to increase first, then decrease, and then increase again, with M6 powder reaching a minimum value of 43oe. Figure 7 (b) shows that the magnetic properties of the alloys after annealing show different changes. The increase in Ms of the two-phase nanocrystalline alloy powders with the same Co content after annealing is due to the precipitation of more α-FeCo phases embedded in the residual amorphous matrix and the increase in crystallinity. The A6 powder reaches a maximum value of 189emu / g, but the decrease in Ms of A0 and A2 is due to the precipitation of more FCC phases and non-soft magnetic Fe 2 Phase B. After annealing, the heat treatment process resulted in the reduction of defects and the release of internal stress, causing the Hc to decrease, and the A8 powder reached a minimum value of 12.8oe.
[0060] Example 4
[0061] In order to study the electromagnetic absorption properties of the prepared powder, the M-Fe 76- x Co x Si 2 B 21 Cu and A-Fe 76-x Co x Si 2 B 21 Complex dielectric constant (ε) of Cu two-phase nanocrystalline powders in the frequency range of 2 to 18 GHz r=ε′-jε″) and complex magnetic permeability (μ r =μ′-jμ″) Figure 8 As shown. The real part (ε′ and μ′) of the complex dielectric constant and complex magnetic permeability represents the storage capacity of electrical and magnetic energy, and the imaginary part (ε″ and μ″) represents the loss capacity of electrical and magnetic energy. The dielectric loss mainly includes polarization loss and conductivity loss. Figure 8 (a) indicates M-Fe 76-x Co x Si 2 B 21 The ε′ of Cu powder shows a slightly decreasing trend in the range of 2-18 GHz, and with the increase of Co content, it first increases, then decreases, and then increases again. Interface polarization is the main mechanism of polarization, and particles with large surface areas have a strong interface polarization effect. Therefore, the size of the flake powder decreases significantly at M6 and M8, and the interface polarization weakens, resulting in a decrease in ε′. In addition, the electrical conductivity σ is also an important factor affecting ε′. Therefore, M0 has the largest flake size but ε′ is still small because the electrical conductivity of the Co-free nanocrystalline powder is low. On the other hand, the fluctuation of ε″ in the range of 2-18 GHz shows obvious polarization relaxation behavior. After annealing, A-Fe 76-x Co x Si 2 B 21 The ε′ of Cu dual-phase nanocrystalline powders increases because the increase in the size of the powder particles after annealing is conducive to the enhancement of surface polarization, among which the increases of A4 and A8 are particularly obvious. In addition, the new phase of the FCC structure precipitated after annealing produces a new phase interface, which promotes interfacial polarization, and the reduction of defects after annealing leads to an increase in dipole interaction, which is conducive to displacement polarization and leads to an increase in ε′. It can be noted that ε″ is significantly negative in the high-frequency region, which may be due to the fact that the powder particles form a conductive grid and radiate electromagnetic waves.
[0062] In the test frequency range, as the frequency increases, the skin effect increases, and the real part μ' of the magnetic permeability of all powders decreases with increasing frequency. At 2GHz, μ' increases with the Co content and then decreases and then increases again. The μ' of M4 powder reaches a maximum value of 2.09. According to the empirical formula of initial magnetic permeability, it can be obtained:
[0063] μi is proportional to the square of Ms. As the Co content increases, Ms first increases, then decreases, and then increases again. It can be inferred that μ′ also shows a trend of first increasing, then decreasing, and then increasing as the Co content increases.
[0064]
[0065] Ms: saturation magnetization; K1: magnetocrystalline anisotropy; λs: magnetostriction coefficient; ε: internal strain; β: impurity volume concentration; δ: domain wall thickness, d: impurity particle size.
[0066] The imaginary part of the magnetic permeability μ″ is an inverted parabola in the entire frequency range, which is caused by the uneven distribution of particles. At the same time, μ″ presents three resonance peaks (4-6GHz, 8-10GHz, 14-16GHz) These resonance peaks can be attributed to natural resonance, eddy current and exchange resonance. According to the eddy current loss formula:
[0067] μ r ″=3πμ 0 (μ′) 2 d 2 fσ (3)
[0068] Among them, f is the frequency of electromagnetic waves, d is the thickness of the absorbing material, σ is the conductivity, μ 0 is the magnetic permeability of free space.
[0069] μ″ is proportional to the square of μ′, so μ″ changes with Co content in the same way as μ′.
[0070] After annealing, with M-Fe 76-x Co x Si 2 B 21 Compared with Cu nanocrystalline powders, the decrease in μ′ of A0 and A2 powders is due to the decrease in Ms and more Fe 2 The increase of Ms and the decrease of Hc will increase μ'. The reduction of internal stress and crystal defects caused by annealing is also conducive to the increase of μ'. Therefore, the μ' of other powders increases. It is worth noting that μ" shows a significant increase after annealing, which improves the magnetic loss capacity of the material.
[0071] In order to further study the M-Fe 76-x Co x Si 2 B 21 Cu and A-Fe 76-x Co x Si 2 B 21 The electromagnetic loss mechanism of the two Cu powders, the dielectric loss tangent value (tanδ ε =ε″ / ε′) and magnetic loss tangent (tanδ μ =μ″ / μ′), which represent the dielectric loss and magnetic loss capacity of the material respectively. Fig. 9 The change curve of the loss tangent value in the range of 2-18GHz is shown. The results show that the magnetic loss tangent value tanδ before and after annealing μMuch larger than the dielectric loss tangent tanδ ε , indicating that magnetic loss plays a major role in the dissipation of electromagnetic wave energy in the entire frequency range. The magnetic loss of the material mainly comes from hysteresis loss, eddy current loss, domain wall resonance, natural resonance and exchange resonance. Hysteresis loss can be ignored in weak magnetic fields. Domain wall resonance is usually observed in multi-domain material systems and generally occurs at lower frequencies (<2GHz). In addition, the eddy current loss of the material can be expressed by the following formula:
[0072] C 0 =μ″(μ′) -2 f -1 (4)
[0073] Where f is the frequency of the electromagnetic wave.
[0074] If the magnetic loss of the material is only related to the eddy current loss, then C 0 The frequency should remain constant, C 0 As frequency changes Fig.10 In fact, M-Fe 76-x Co x Si 2 B 21 Cu powder C 0 As the frequency increases to 7GHz, it gradually decreases, and then C 0 As the frequency increases further, it fluctuates, so M-Fe 76-x Co x Si 2 B 21 The magnetic loss of Cu powder to electromagnetic waves includes not only eddy current loss, but also natural resonance and exchange resonance. The exchange resonance appears in the high frequency region. Figure 8 The magnetic resonance peaks of μ″ at 4.5 GHz and 8.5 GHz are natural resonances, and the magnetic resonance peak at 14.5 GHz is an exchange resonance. 76-x Co x Si 2 B 21 Cu powder C 0 It gradually decreases with increasing frequency and then remains relatively stable in the high frequency region. 76-x Co x Si 2 B 21 The magnetic loss of Cu powder includes natural resonance and exchange resonance, and the main loss is eddy current loss in the high frequency region.
[0075] The absorption capacity of a material to electromagnetic waves can be expressed by the reflection loss value (RL). According to the transmission line theory, the reflection loss value (RL) can be calculated by combining the measured electromagnetic parameters and the thickness of the absorbing layer. The formula is:
[0076]
[0077]
[0078] Z in is the wave impedance of the medium; Z 0 is the free space wave impedance; μ r is the complex magnetic permeability; ε r is the complex dielectric constant; f is the incident wave frequency; d is the thickness of the absorbing layer; c is the speed of light in vacuum; j is the imaginary unit.
[0079] Fig.11 and Fig.12 The calculated M-Fe 76-x Co x Si 2 B 21 Cu and A-Fe 76-x Co x Si 2 B 21 Contour plot of reflection loss (RL) of two Cu powders as a function of thickness and frequency and the specific RL of each powder min 、f m , Δf RL<-10 and d m It is generally believed that the frequency range where RL < -10dB corresponds to 90% microwave absorption is generally accepted as the effective absorption bandwidth (Δf RL<-10 ).from Fig.12 It can be seen that with the increase of Co content, the absorption performance of M6 powder is the best. At 12.32GHz, the best reflection loss (RL min ) reaches -59.51dB, Δf when d is 1.69mm RL<-10 The maximum width reaches 7.68GHz (10.08~17.76GHz), basically covering the entire Ku band (12~18GHz) and part of the X band (8~12GHz). The effective bandwidth Δf at a thickness of 2.09mm RL<-10 is 5.12GHz (8.00~13.12GHz), covering the entire X-band. 76-x Co x Si 2 B 21 Cu powder, M0 powder has the smallest RL min is -50.71dB, but still exceeds -50dB, RL minThe corresponding f all exceeds 10GHz, and d is less than 2mm, which is kept at a low level. At about 1.66mm, the optimal effective absorption bandwidth ΔfRL<-10 of all powders exceeds 7.5GHz. Compared with the unannealed powder, the frequency corresponding to the optimal reflection loss (RLmin) after annealing moves to the low frequency region. This is due to the increase in magnetic permeability μr and dielectric constant εr. The optimal reflection loss (RLmin) of powders with multiple Co contents after annealing is more outstanding. In general, by adjusting the Co content and annealing to achieve the regulation of electromagnetic parameters, the material can have a more excellent electromagnetic wave absorption performance.
[0080] The reflection loss of the material is related to the impedance matching characteristics and attenuation coefficient. The impedance matching calculation formula is: Z = |Z in / Z 0 |, the closer Z is to 1, the better the material impedance matching is, which allows more electromagnetic waves to enter the absorbing material, and the reflection of electromagnetic waves is close to zero, thereby improving the material's absorbing performance. The attenuation coefficient (α) reflects the material's ability to attenuate electromagnetic waves and can be used to evaluate the synergistic enhancement of dielectric loss and magnetic loss. Fig.13 As shown in the figure. When dm is 1.8mm, the impedance matching is the best and the attenuation coefficient is excellent at 12.32GHz, achieving excellent electromagnetic wave absorption performance. At higher frequencies, although the attenuation coefficient is even better, the impedance of M6 at different thicknesses is obviously mismatched, which leads to a decrease in electromagnetic wave absorption performance.
[0081] The present invention successfully prepares a micron-level dual-phase nanocrystalline alloy material with excellent electromagnetic wave absorption performance by single-roll belt spinning combined with vacuum mechanical ball milling. The optimal reflection loss (RLmin) of M6 powder at 12.32GHz and d of 1.8mm reaches -59.50dB, and when d is 1.69mm, ΔfRL<-10 reaches a maximum width of 7.68GHz (10.08-17.76GHz), basically covering the entire Ku band (12-18GHz) and part of the X band (8-12GHz). The soft magnetic nanocrystalline phase has high saturation magnetization and low coercive force, improves the initial magnetic permeability, and has a strong magnetic loss capacity. At the same time, the non-metallic elements contained in the dual-phase nanocrystalline alloy powder and the presence of the amorphous phase make its resistivity higher, suppress eddy current loss, and have a lower dielectric constant, which optimizes the impedance matching capability. By adjusting the Co content and annealing to achieve the regulation of electromagnetic parameters, the material can have more excellent electromagnetic wave absorption performance.
[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A Fe with excellent electromagnetic absorption performance 76-x Co x SiC 21 Cu dual-phase nanocrystalline powder, characterized in that: The chemical formula of the dual-phase nanocrystalline powder is Fe 76-x Co x SiC 21 Cu, wherein x=0-10.
2. The Fe alloy having excellent electromagnetic absorption performance as claimed in claim 1 76-x Co x SiC 21 Cu dual-phase nanocrystalline powder, characterized in that: Said x=0, 2, 4, 6, 8 or 10.
3. A Fe with excellent electromagnetic absorption performance 76-x Co x SiC 21 The method for preparing Cu dual-phase nanocrystalline powder is characterized in that: include: Under the protection of inert atmosphere, Fe, Co, Si, Cu and FeB are mixed and smelted to obtain Fe 76-x Co x SiC 21 Cu alloy ingot; Fe was prepared by single copper roller melt spinning process. 76-x Co x SiC 21 Cu amorphous strip; The Fe 76-x Co x SiC 21 Cu amorphous strips were cut to less than 1 mm, ball-milled, and annealed to obtain Fe 76-x Co x SiC 21 Cu dual-phase nanocrystalline powder; Wherein, x=0-10.
4. The Fe alloy having excellent electromagnetic absorption performance as claimed in claim 3 76-x Co x SiC 21 The method for preparing Cu dual-phase nanocrystalline powder is characterized in that: The mass fraction of Fe is 99.99% or more; Or, the mass fraction of Co is 99.98% or above; Or, the mass fraction of Si is 99.9999% or more; Or, the mass fraction of Cu is 99.99% or above; Or, in the FeB, the mass ratio of Fe to B is 5:
1.
5. The Fe alloy having excellent electromagnetic absorption performance as claimed in claim 3 76-x Co x SiC 21 The method for preparing Cu dual-phase nanocrystalline powder is characterized in that: The Fe 76-x Co x SiC 21 The thickness of the Cu amorphous strip is 20-25 mm and the width is 1.5-2 mm; Or, the thickness is 25 μm and the width is 2 mm.
6. The Fe alloy having excellent electromagnetic absorption performance as claimed in claim 3 76-x Co x SiC 21 The method for preparing Cu dual-phase nanocrystalline powder is characterized in that: The ball milling adopts vacuum ball milling.
7. The Fe alloy having excellent electromagnetic absorption performance as claimed in claim 6 76-x Co x SiC 21 The method for preparing Cu dual-phase nanocrystalline powder is characterized in that: The conditions of the vacuum ball milling are: a ball-to-material weight ratio of 30-32:1, a rotation speed of 500-600 rpm, and a rotation of 0.5-0.6 h, followed by a pause of 5-8 min during the ball milling process, with forward and reverse rotations performed alternately.
8. The Fe alloy having excellent electromagnetic absorption performance as claimed in claim 3 76-x Co x SiC 21 The method for preparing Cu dual-phase nanocrystalline powder is characterized in that: The annealing treatment is carried out in an inert atmosphere, the annealing temperature is 673-678K, and the annealing time is 1-1.5h.
9. Annealing and Co content in regulating Fe 76-x Co x SiC 21 Application of Cu dual-phase nanocrystalline powder in microwave absorption properties.
10. Fe according to claim 1 or 2 76-x Co x SiC 21 Application of Cu dual-phase nanocrystalline powder in the preparation of electromagnetic absorption materials.
Citation Information
Patent Citations
Iron-based nanometer crystal magnetically soft alloy and preparation method thereof
CN102543347A
Iron-based nanocrystalline magnetically soft alloy material and preparation method thereof
CN102719746A
Preparation method of iron-based nano polyphase alloy powder containing transition metal elements and application of iron-based nano polyphase alloy powder in azo dye wastewater treatment
CN107538014A
Iron base nanocrystal magnetically soft alloy micropowder electromagnetic wave absorbing agent and preparation method thereof
CN109732078A
Core-Shell Structured Composite Powder Electromagnetic Wave Absorber Formed by Coating Fe-Based Nanocrystalline Alloy with Carbon, and Preparation Method Thereof
US20220380609A1